Baker, Herbert (Sir) and Masey. New Modderfontein additions to hospital. Nov 1909. Plans sections and elevations. Ink and watercolour paints on parchment. - Baker & Masey, Herbert (Sir) (My University, 2012)
Baker, Herbert (Sir) and Masey. New Modderfontein additions to hospital. Nov 1909. Plans sections and elevations. Ink and watercolour paints on parchment.
Ink & watercolour paints on parchment. 670X945
Keywords: Baker, Herbert (Sir) and Masey. New Modderfontein additions to hospital. Nov 1909. Plans sections and elevations. Ink and watercolour paints on parchment.